Film Tourism: A Contemporary Resource for Promoting Serbia - Dejan Berić (Turizam, 2013)
Studies of the relationships between film, TV and tourism are relatively new, and in development mainly since the early 1990s. Leisure activities such as watching films as well as traveling are ways to escape. Both provide temporary relief from the real world. Contemporary tourism industry itself is very competitive and many new destinations are trying to attract the tourists to their destinations. Film can provide knowledge of certain aspects of the country such as nature, culture and people which result in the construction of the attitudes towards the country. An interest in the nation and its positive image can eventually lead to an actual visit to the country. Serbia offers a range of scenery that can serve diverse location needs from villages to rivers, mountains and forests. The country’s unique architecture from Ottoman and Habsburg to Socialist period structures and from Roman and Medieval to contemporary urban is offering rich, distinct backdrops for a variety of productions. This paper investigates the film tourism phenomenon by reviewing previous research and practices (in several countries, including Serbia) to highlight the benefits of film in promoting tourist products.